Application of cayley differential unitary space-time code in multiple-input multiple-output power line communication - Jiaxin DING; Liangfang NI; Yi WANG; Huijie DAI (Dianxin kexue)
The application of Cayley differential unitary space-time code in MIMO power line communication system was studied.The linear space of complex skew-Hermitian matrices was mapped to isotropic unitary matrix constellations represented by highly non-linear Stiefel manifolds,by which signals were transmitted through a block fading multiple input multiple output power line channel with in a differential mode.Finally,based on the unconstrained solution of the Cauchy random by which data streams were represented,the approximate linear maximum likelihood estimation of the transmitted signal was induced.Simulation results show that although the performance of the proposed scheme is slightly lower than that of the system based on orthogonal differential space-time code in terms of bit error rate and diversity gain,it can ensure high-speed and reliable communication at higher signal-to-noise ratios,and is suitable for multi-input multi-output power line communication systems requiring high-speed data transmission.